Kehadiran Acanthamoeba spp. pada bekas penyimpanan kanta sentuh pengguna asimptomatik - Putri Noradyani Megat Hashim,; Mohamed Kamil Abdul Ghani,; Norhayati Moktar,; Anisah Nordin,; Yusof Suboh,; Mimi Fazah Zainudin,; Noraina Abdul Rahim, (penerbit ukm, 2007)
Acanthamoeba keratitis, a type of corneal inflammation associated with contact lense usage is caused by Acanthamoeba sp., a free-living amoeba found in various kind of human environment. Contamination of contact lens storage containers by Acanthamoeba spp. Leads to the amoeba adhering to the lens thus infecting the eye. The objective of this study is to examine for the presence of Acanthamoeba spp in the contact lens storage containers of asymptomatic users. Ninety asymptomatic contact lens users participated in this study. Samples were taken by swabbing of contact lens containers and cultured them onto non-nutrient agar with overlaid Escherichia coli. Plates were examined daily for the presence of amoeba. The positive cultures were then confirmed under ‘Image Analysis with Video TesT 4.0’. Eight of 90 samples (8.7%) were positives for Acanthamoeba spp. And all strains identified were from group II (polyphagids). This finding suggests that Acanthamoeba spp. Can contaminate the storage lens containers of asymptomatic lens users thus can be a major risk factor for Acanthamoeba keratitis.